2005
DOI: 10.1093/bioinformatics/bti811
|View full text |Cite
|
Sign up to set email alerts
|

Lateral gene transfer of a dermonecrotic toxin between spiders and bacteria

Abstract: We use superpositions of recently determined structures and sequence comparisons to infer that both bacterial and spider SMaseDs originated from a common, broadly conserved domain family, the glycerophosphoryl diester phosphodiesterases. We also identify a unique sequence/structure motif present in both SMaseDs but not in the ancestral family, supporting SMaseD origin through a single divergence event in either bacteria or spiders, followed by lateral gene transfer from one lineage to the other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 18 publications
1
32
3
Order By: Relevance
“…This enzyme display broad specificity for glycerophosphodiesters, glycerophosphocholine, glycerophosphoethanolamine, glycerophosphoglycerol and bis (glycerophosphoglycerol), all of which are hydrolysed by this enzyme. This gene also has been reported to be involved in HGT between spider and bacteria [40]. Expression analysis suggested that this gene was not only highly expressed in integument and fat body but also in midgut and hemocyte.…”
Section: Resultsmentioning
confidence: 98%
“…This enzyme display broad specificity for glycerophosphodiesters, glycerophosphocholine, glycerophosphoethanolamine, glycerophosphoglycerol and bis (glycerophosphoglycerol), all of which are hydrolysed by this enzyme. This gene also has been reported to be involved in HGT between spider and bacteria [40]. Expression analysis suggested that this gene was not only highly expressed in integument and fat body but also in midgut and hemocyte.…”
Section: Resultsmentioning
confidence: 98%
“…Smase D enzymes in both lineages contain similar C-terminal plug motifs and, in the absence of phylogenetic analyses, the disjunct presence of this motif in both lineages was put forward as evidence for a lateral gene transfer event (32 …”
Section: Sphingomyelinase Dmentioning
confidence: 99%
“…This scenario gains support from the fact that both the fungal and the tick enzymes contain C-terminal plug motifs that differ from the identical motifs in the bacterial and spider toxins. In SmaseD of both Corynebacterium (bacteria) and Loxosceles (spider), Asn residues at position 278 contribute a backbone hydrogen bond, causing subsequent residues to form a type-I β-turn, which blocks the N-terminal end of the TIM (triosephosphate isomerase) barrel (32). In the enzymes of the tick, fungi, and non-Corynebacterium bacteria, various other residues occupy position 278 (Asp in the tick; Ala, Lys, Ser, or Thr in fungi; and Ile in Arcanobacterium), potentially affecting the plugging of the barrel.…”
Section: Figurementioning
confidence: 99%
“…8, below). GDPDs are distantly related to the SicTox proteins (27,64,65), and their mechanism has been proposed to proceed through a five-membered cyclic phosphate intermediate (45) analogous to the product of the toxin action on lysophospholipids (15). We felt that the conformation of the glycerol phosphate in the GDPD active site was a reasonable model for the phosphoglycerol portion of LPC or LPE bound to the toxin in a catalytically competent mode.…”
Section: Structural Comparison Of St_␤ib1i With Other Sictox Proteinsmentioning
confidence: 99%
“…One possibility is that the SicTox mechanism is homologous to the first step of the mechanism of GDPD enzymes, which are distantly related (27,64,65). GDPDs hydrolyze phosphoglycerol substrates and have been proposed to form a cyclic intermediate analogous to the lipid product of the action of SicTox enzymes on lysophospholipids (45).…”
Section: Structural Comparison Of St_␤ib1i With Other Sictox Proteinsmentioning
confidence: 99%